Sustainable microgrids with energy storage as a means to increase power resilience in critical facilities: An application to a hospital. (July 2020) - Lagrange, Alexis; de Simón-Martín, Miguel; González-Martínez, Alberto; Bracco, Stefano; Rosales-Asensio, Enrique
Highlights: An optimal microgrid considering power resilience for a hospital was designed. Economical profit and minimum resilience were considered for components sizing. Up to 12 scenarios have been analyzed in REopt® observing a significant impact. Positive net savings and more than 1 day of minimum survival time can be achieved. Abstract: This manuscript proposes to study different cases that require the use of renewable energies in addition to diesel generators and energy storage systems with the aim of increasing the resilience of a microgrid feeding critical facilities. The aim of the work here presented is to quantify the benefits provided by an improvement of the energy resilience that could be achieved by installing a microgrid in a hospital fed by renewable energy sources. The microgrid will use a scheme based on solar PV in addition to diesel generators and an energy storage system based on electrochemical batteries. First, it has been evaluated how the implant of the microgrid increases the resilience of the power supply when a power failure occurs, considering that the main application in a hospital, even in the event of breakdowns, is to ensure the continuity of the surgical procedures and safely store drug stocks. Thus, these have been defined as the critical loads of the system. The components sizes have been optimized by considering both economic profitability but also the resilience capacity, observing that, by installing solar photovoltaic modules, Li-ion batteries and diesel generators, according to simulations performed in REopt ® software, the microgrid could save approximately $ 440, 191 on average over a 20-year life cycle of the facility (both considering the mitigation of energy provide by the power grid and the avoided losses during probable power services interruptions), while increasing the minimum resilience of the installation more than 34 h.